The relationship between metabolic dysfunction-associated fatty liver disease and the incidence rate of extrahepatic cancer - Wei, Suosu; Hao, Yanrong; Dong, Xiaofeng; Huang, Junzhang; Huang, Kai; Xie, Yujie; Liu, Hongjun; Wei, Chunyu; Xu, Jinan; Huang, Wei; Dong, Lingguang; Yang, Jianrong (Frontiers in Endocrinology, 2023)
Background The associations between metabolic dysfunction-associated fatty liver disease (MAFLD) and cancer development, especially extrahepatic cancers, are unknown. The aims of the current study were to investigate the cancer incidence rates of MAFLD and analyze the associations between MAFLD and the development of cancers. Methods This historical cohort study included participants who underwent ultrasonographic detection of hepatic steatosis at a tertiary hospital in China from January 2013 to October 2021. MAFLD was diagnosed in accordance with The International Expert Consensus Statement. Cox proportional hazards regression modeling was used to assess the associations between MAFLD and the development of cancers. Results Of the 47,801 participants, 16,093 (33.7%) had MAFLD. During the total follow-up of 175,137 person-years (median 3.3 years), the cancer incidence rate in the MAFLD group was higher than that in the non-MAFLD group [473.5 vs. 255.1 per 100,000 person-years; incidence rate ratio 1.86; 95% confidence interval (CI) 1.57–2.19]. After adjustment for age, gender, smoking status, and alcohol status, MAFLD was moderately associated with cancers of the female reproductive system/organs (labium, uterus, cervix, and ovary) [hazard ratio (HR) 2.24; 95% CI 1.09–4.60], thyroid (HR 3.64; 95% CI 1.82–7.30), and bladder (HR 4.19; 95% CI 1.15–15.27) in the total study cohort. Conclusion MAFLD was associated with the development of cancers of the female reproductive system/organs (labium, uterus, cervix, and ovary), thyroid, and bladder in the total study cohort.